2005
DOI: 10.1088/0960-1317/15/5/001
|View full text |Cite
|
Sign up to set email alerts
|

Modelling squeeze film effects in a MEMS accelerometer with a levitated proof mass

Abstract: A triaxial accelerometer is presented which employs as its proof mass a mechanically free micromachined disc that is electrostatically levitated. Air damping plays a critical role in the operation of the accelerometer, providing stability to an inherently unstable system. Systems that operate beyond the cut-off frequency, however, suffer reduced gain due to the spring component of the squeeze film damping, resulting in decreased sensitivity. A finite-element model for extracting squeeze film damping coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…The BNEA is expressed as: italicBNEA=4kBTωnitalicmQ[m/s2/Hz1/2]where k B is the Boltzmann constant (1.38 × 10 −23 m 2 kg/s 2 /K), T is the absolute room temperature (300 K), ω n is the 1st mode natural frequency of the microacceleromter, m is the mass, and Q is the mechanical quality factor. For an analysis of the mechanical quality factor, the squeeze film damping model [20,21] is applied between movable proof mass and substrate. According to [22], the Stoke’s flow damping between the interdigitated comb electrodes is negligible compared to the squeeze film damping between two plates.…”
Section: Mems Sensing Element Designmentioning
confidence: 99%
“…The BNEA is expressed as: italicBNEA=4kBTωnitalicmQ[m/s2/Hz1/2]where k B is the Boltzmann constant (1.38 × 10 −23 m 2 kg/s 2 /K), T is the absolute room temperature (300 K), ω n is the 1st mode natural frequency of the microacceleromter, m is the mass, and Q is the mechanical quality factor. For an analysis of the mechanical quality factor, the squeeze film damping model [20,21] is applied between movable proof mass and substrate. According to [22], the Stoke’s flow damping between the interdigitated comb electrodes is negligible compared to the squeeze film damping between two plates.…”
Section: Mems Sensing Element Designmentioning
confidence: 99%
“…For higher values of σ, the compressibility leads to a significant air-spring effect, which can be undesirable as it can adversely affect the dynamic behavior of a device [10]. Contrary to this, the fact that perforations increase the cutoff frequency-the frequency at which the damping and spring forces are equal-can be exploited by suitably tuning both of these forces by varying the number and size of perforations [11]. Blech [12] and Allen et al [13] have also reported the use of squeeze-film damping to tailor the frequency response of a seismic accelerometer and that of micromachined sensors, respectively.…”
Section: B Compressibilitymentioning
confidence: 99%
“…The coefficients A and B in (11) are evaluated by substituting the boundary conditions for the pressure cell approximated within a particular pattern. These boundary conditions can be taken as Φ| R i = 0 and ∂Φ/∂R| R o = 0, where R o and R i are the normalized outer and inner radii of the circular pressure cell, respectively.…”
Section: A Modified Reynolds Equation With Inertia Compressibilitymentioning
confidence: 99%
“…The stiffness and damping constants due to a squeeze-film effect were estimated from ANSYS simulations of the rotor under an operating pressure of 20 mtorr. The estimations were carried out using a method described in references [18,24]. All of the parameters are summarized in Table 1.…”
Section: Device Parameters and Estimated Performancementioning
confidence: 99%